In vivo digestibility in guinea pigs fed with four varieties of Brachiaria spp (Revista Sistemas de Producción Agroecológicos, 2016)
The development in the production of guinea pig (Cavalia porcellus), as an alternative source of protein for the population, is an initiative that has been gaining strength in Colombia; considering that the species Brachiaria grasses, represent a source of fiber and energy for the tropics, its inclusion in diets for C. porcellus is limited by the lack of information on its nutritional value and digestive harnessing in these animals, therefore, the objective of this study was to determine the nutritional value and digestibility coefficients of dry matter (DM), crude protein (CP), fat (GR) and crude fiber (CF), and estimate the nitrogen-free extract (ENN), percentage of total digestible nutrients (TDN), gross energy (Mcal/kg MS) (EB), digestible ( ED) and metabolic (EM). The forages and treatments used were: (Brachiaria hybrid cv. mulato (T1), Brachiaria decumbens cv. amargo (T2), Brachiaria brizantha cv. toledo (T3) and Brachiaria brizantha cv. marandú (T4). For the experiment twelve creole male Cavalia porcellus were used, with an average weight of 778 ± 10 g, installed in metabolic cages, distributed in a completely randomized design with four treatments, four species of Brachiaria and three replicates each one. The amount of forage consumed ad libitum was weighty, and also, they were collected and weighed feces for six days, to later analyze them in the laboratory, in order to estimate their digestibility coefficients and energy distribution. Digestibility coefficients of MS were higher (P
Keywords: Cavia porcellus; grasses; digestibility; minor species